If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x) = 8x + -3 Reorder the terms: 6x = -3 + 8x Solving 6x = -3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6x + -8x = -3 + 8x + -8x Combine like terms: 6x + -8x = -2x -2x = -3 + 8x + -8x Combine like terms: 8x + -8x = 0 -2x = -3 + 0 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5
| 0=7/3x-7/2 | | 2/3(x)^2+7/3(x)=5 | | -16-10x=2(-7x+6) | | (x-7)*(x-6)= | | X-6=2x+12 | | 2/3x^2+7/3=5 | | d+c+(b-10)+(b+10)=360 | | (x-7)*(x+6)= | | 2a^2-a-12=2 | | 7m+15=9m-75 | | (4/8)(2/3)(1/5) | | X-6=2x-24 | | u(6u+5)=1 | | 6=-15x | | (3/5-3/10)*30 | | 76=-4m | | h=-16t^2+56t+40 | | x^3/2=14 | | 2(3.14)(12)= | | 0.125x=-3 | | b/2+5=-7 | | Y/3=15 | | 8c=-122 | | 2(z-x)=5x-(3x+2) | | 25/57=849/5x | | w^8+11w^4+10= | | 7x+5y=9 | | y=2/5-2 | | 8b+11-3b=2b-3+5 | | 3/4x-7=17 | | 4x^2+17=5 | | (45-27)n= |